Longitudinal changes in task-evoked brain responses in Parkinson's disease patients with and without mild cognitive impairment - Ekman, Urban; Eriksson, Johan; Forsgren, Lars; Domellöf, Magdalena E.; Elgh, Eva; Lundquist, Anders; Nyberg, Lars (Frontiers in Neuroscience, 2014)
Cognitive deficits are common in Parkinson’s disease. Previous cross-sectional research has demonstrated a link between cognitive impairments and fronto-striatal dopaminergic dysmodulation. However, longitudinal studies that link disease progression with altered task-evoked brain activity are lacking. Therefore, our objective was to longitudinally evaluate working-memory related brain activity changes in Parkinson’s disease patients with and without mild cognitive impairment. Patients were recruited within a longitudinal cohort study of incident patients with idiopathic parkinsonism. We longitudinally (at baseline examination and at 12-months follow-up) compared 28 patients with Parkinson’s disease without mild cognitive impairment with 11 patients with Parkinson’s disease and mild cognitive impairment. Functional MRI blood oxygen level dependent signal was measured during a verbal two-back working-memory task. Patients with mild cognitive impairment under-recruited bilateral medial prefrontal cortex, right putamen, and lateral parietal cortex at both time-points (main effect of group: p<0.001, uncorrected). Critically, a significant group-by-time interaction effect (p<0.001, uncorrected) was found in the right fusiform gyrus, indicating that working-memory related activity decreased for patients with Parkinson’s disease and mild cognitive impairment between baseline and follow-up, while patients without mild cognitive impairment were stable across time-points. The functional connectivity between right fusiform gyrus and bilateral caudate nucleus was stronger for patients without MCI relative to patients with MCI. Our findings support the view that deficits in working-memory updating are related to persistent fronto-striatal under-recruitments in patients with early phase Parkinson’s disease and mild cognitive impairment. The longitudinal evolution of mild cognitive impairment in Parkinson’s disease translates into additional task-evoked posterior cortical changes.